Elucidating connections between the strigolactone biosynthesis pathway, flavonoid production and root system architecture in Arabidopsis thaliana. Issue 2 (11th April 2022) - Richmond, Bethany L.; Coelho, Chloe L.; Wilkinson, Helen; McKenna, Joseph; Ratchinski, Pélagie; Schwarze, Maximillian; Frost, Matthew; Lagunas, Beatriz; Gifford, Miriam L.
Abstract: Strigolactones (SLs) are the most recently discovered phytohormones, and their roles in root architecture and metabolism are not fully understood. Here, we investigated four MORE AXILLARY GROWTH ( MAX ) SL mutants in Arabidopsis thaliana, max3‐9, max4‐1, max1‐1 and max2‐1, as well as the SL receptor mutant d14‐1 and karrikin receptor mutant kai2‐2 . By characterising max2‐1 and max4‐1, we found that variation in SL biosynthesis modified multiple metabolic pathways in root tissue, including that of xyloglucan, triterpenoids, fatty acids and flavonoids. The transcription of key flavonoid biosynthetic genes, including TRANSPARENT TESTA4 ( TT4 ) and TRANSPARENT TESTA5 ( TT5 ) was downregulated in max2 roots and seedlings, indicating that the proposed MAX2 regulation of flavonoid biosynthesis has a widespread effect. We found an enrichment of BRI1‐EMS‐SUPPRESSOR 1 (BES1) targets amongst genes specifically altered in the max2 mutant, reflecting that the regulation of flavonoid biosynthesis likely occurs through the MAX2 degradation of BES1, a key brassinosteroid‐related transcription factor. Finally, flavonoid accumulation decreased in max2‐1 roots, supporting a role for MAX2 in regulating both SL and flavonoid biosynthesis.